Type 1 Diabetes Mellitus in Saudi Arabia: A Soaring Epidemic - Asirvatham Alwin Robert; Abdulrahman Al-Dawish; Muhammad Mujammami; Mohamed Abdulaziz Al Dawish (International Journal of Pediatrics)
Type 1 diabetes mellitus (T1DM) is quite prevalent in the world, with a proportion of 1 in every 300 persons and steadily rising frequency of incidence of about 3% every year. More alarmingly, the incidence of T1DM among infants is also increasing, with children as young as 6 months succumbing to it, instead of that at a rather established vulnerable age of around seven and near puberty, when the hormones antagonize the action of insulin. These reports pose a unique challenge of developing efficient T1DM management system for the young children. The Kingdom of Saudi Arabia (KSA) is the largest country in the Middle East that occupies approximately four-fifths of the Arabian Peninsula supporting a population of more than 33.3 million people, of whom 26% are under the age of 14 years. As per the Diabetes Atlas (8th edition), 35,000 children and adolescents in Saudi Arabia suffer from T1DM, which makes Saudi Arabia rank the 8th in terms of numbers of TIDM patients and 4th country in the world in terms of the incidence rate (33.5 per 100,000 individuals) of TIDM. However, in comparison with that in the developed countries, the number of research interventions on the prevalence, incidence, and the sociodemographic aspects of T1DM is woefully inadequate. In this review we discuss different aspects of T1DM in Saudi Arabia drawing on the published literature currently available.